2012
DOI: 10.1177/1076029612465669
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Neutrophil to Lymphocyte Ratio in Clinical Outcomes of Non-ST Elevation Myocardial Infarction and Unstable Angina Pectoris

Abstract: We sought to determine the prognostic value of neutrophil to lymphocyte ratio (NLR) in non-ST elevation myocardial infarction (NSTEMI) and unstable angina pectoris (UAP). A total of 308 (mean age 59.22 ± 11.93) patients with NSTEMI and UAP were prospectively evaluated. The study population was divided into tertiles based on admission NLR values. The patients were followed for clinical outcomes for up to 3 years after discharge. In the Kaplan-Meier survival analysis, 3-year mortality was 21.6% in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
11
32
0
Order By: Relevance
“…NLR AUC in our study in HTX showed better performance for in‐hospital mortality compared with the AUC for predicting major adverse cardiovascular events after percutaneous coronary interventions,26 or saphenous vein graft disease,27 and atrial fibrillation20 after CABG. On the contrary, other studies have showed better NLR AUC for mortality both in HF28, 29 and in non‐ST elevation myocardial infarction 30. The results for PLR were different, and most studies have showed a better predictive value in ST elevation myocardial infarction,13, 14, 15 HF,28, 29 and transcatheter aortic valve replacement,21 and after percutaneous coronary interventions26 or after implantable cardioverter defibrillator placement 18.…”
Section: Discussionmentioning
confidence: 98%
“…NLR AUC in our study in HTX showed better performance for in‐hospital mortality compared with the AUC for predicting major adverse cardiovascular events after percutaneous coronary interventions,26 or saphenous vein graft disease,27 and atrial fibrillation20 after CABG. On the contrary, other studies have showed better NLR AUC for mortality both in HF28, 29 and in non‐ST elevation myocardial infarction 30. The results for PLR were different, and most studies have showed a better predictive value in ST elevation myocardial infarction,13, 14, 15 HF,28, 29 and transcatheter aortic valve replacement,21 and after percutaneous coronary interventions26 or after implantable cardioverter defibrillator placement 18.…”
Section: Discussionmentioning
confidence: 98%
“…A relative lymphocytopenia has been reported to be an early marker of myocardial infarction [25] and is associated with increased long-term mortality in patients with CAD [26]. NLR is a combination of these two biomarkers involved in the inflammatory process of atherosclerosis, and has been shown to predict adverse cardiovascular events in STEMI [27,28], non-ST-segment elevation acute coronary syndrome [29][30][31], and stable CAD [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio (NLR) predicts short-term and long-term adverse outcomes in various clinical settings, including ST-segment elevation myocardial infarction [1][2][3][4], non-ST-segment elevation acute coronary syndrome [2,5,6], and stable coronary artery disease (CAD) [7,8]. Recently, NLR has been reported to independently predict cardiovascular mortality in an asymptomatic general population [9].…”
Section: Introductionmentioning
confidence: 99%